Global risks of economic espionage, industrial spying and international trade secrets - Nasheri, Hedi (Henry Stewart Talks, 2009)
Information age threat spectrum, The internet, Threats to infrastructure, Interdependence: new risks and vulnerabilities, "New age crime", Weapons of mass disruption, Enforcement measures, E-commerce, Fraud, Trade secrets, Technology in law enforcement
Archived at 2022/04/03